백내장수술을 받은 만성 신부전 환자의 혈액투석 전후 심한 안압 변동 1예 - 주찬웅; 박성표; 나경익 (검안 및 콘택트렌즈 학회지, 20(4), 2021)
목적: 백내장수술 시행 후 혈액투석 전후로 심한 안압 변동을 보인 만성 신부전 환자 1예를 보고하고자 한다. 증례요약: 만성 신부전으로 혈액투석 중인 51세 여자 환자가 양안 증식당뇨망막병증 및 우안 백내장으로 경과 관찰을 하던 중 우안시력저하를 주소로 내원하였다. 우안 백내장에 대해 수정체유화술 시행 중 섬모체소대 해리와 후낭파열이 발생하였고, 섬모체고랑인공수정체삽입술을 시행하였다. 수술 후 3일째 혈액투석 후 환자는 두통을 동반한 우측 안통을 호소하였고, 우안 안압이 44 mmHg 로 상승하였으며 안구전방 내 경도의 염증과 하측 전방각의 수정체 잔류물이 확인되었다. 안압하강제 투여, 전방천자 및 전방세척으로 환자의 주관적 증상 호전과 함께 안압은 낮아졌으나, 이후에도 혈액투석 후 위와 같은 증상을 동반한 심한 안압상승이 재차 발생하였다. 백내장수술 후 1개월까지 혈액투석 전후로 안압 변동이 반복되어 안압하강수술을 고려하였으나 이후 안압이 안정되어 경과 관찰하였다. 결론: 만성 신부전으로 혈액투석을 받는 환자의 백내장수술 후 수정체 잔류물 및 잔여 점탄물질로 인한 염증과 방수유출능의 감소가 혈액투석 전후의 심한 안압 변동의 원인이 될 수 있다. Purpose: To report a case of severe intraocular pressure fluctuation following hemodialysis after cataract surgery in a patient with chronic renal failure. Case summary: A 51-year-old female patient on hemodialysis for chronic renal failure, who was seen regularly by our retina clinic for proliferative diabetic retinopathy and right eye cataract, presented with decreased visual acuity in her right eye. During phacoemulsification under the diagnosis of right eye cataract, zonular dialysis and posterior capsule rupture occurred and intraocular lens ciliary sulcus insertion was performed. Following hemodialysis 3 days after the surgery, the patient complained of headache and right eye pain. The intraocular pressure of the right eye had increased to 44 mmHg. Mild inflammation in the anterior chamber was found with remnant lens material present at the inferior anterior angle. The use of glaucoma eye drops, anterior chamber paracentesis, and anterior chamber irrigation reduced the intraocular pressure and improved the patient’s symptoms. However, a severe increase in intraocular pressure recurred with the above symptoms, again following hemodialysis. Intraocular pressure fluctuation was repetitively present after serial hemodialysis treatments for 1 month, at which point cataract and glaucoma surgeries were considered. However, the intraocular pressure stabilized afterwards; thus, the patient remained under observation and was treated with glaucoma eye drops. Conclusions: Inflammation and a decrease in the aqueous outflow facility due to remnant lens material and the use of an ophthalmic viscoelastic device in cataract surgery may cause severe intraocular pressure fluctuations in patients undergoing hemodialysis for chronic renal failure. KCI Citation Count: 0